Anatomic Features of C-shaped Mandibular Second Molars in a Selected Iranian Population Using CBCT - Janani, Maryam; Rahimi, Saeed; Jafari, Farnaz; Johari, Masoomeh; Nikniaz, Shabnam; Ghasemi, Negin (Iranian Endodontic Journal, 2019)
Introduction: The aim of this retrospective study was to analyze the frequency of C-shaped root canal configuration and characterize mandibular root canal morphology using cone-beam computed tomography (CBCT) with 3D images in an Iranian population. Methods and Materials: This study consisted of retrospective evaluation of CBCT images from 231 adult patients (153 with bilateral second mandibular molars). Two endodontists examined 384 mandibular second molars of a population in Tabriz, Iran to determine the presence of C-shaped canals and their anatomical characteristics. Root canal configurations were categorized at three different levels. Bilateral or unilateral occurrence of C-shaped canals and their relationship to gender, age and tooth position were examined and statistically analyzed using chi squared test and Fisher’s exact test in SPSS 17. The significance level was set at 0.05. Results: Of 384 mandibular second molars examined, 82 (21.4%) molars from 58 patients had a C-shaped root canal configuration. The prevalence of bilateral C-shaped canals was 15.6% amongst 153 patients with bilateral mandibular second molars. There were no significant differences in the distribution of C-shaped canals with respect to gender or age (P=0.06 and P=0.86, respectively). Only 4 teeth (4.9%) had the same root canal configuration from the orifice to the apex. In the remainder of the teeth, the cross-sectional root canal configuration changed at different levels of the root. Conclusion: There were significant variations in the number of roots and canal morphology in mandibular second molars, which should be considered during debridement and obturation of the root canal system. Keywords: C-shaped Canal; Canal Configuration; Cone-beam Computed Tomography; Mandibular Second Molar